SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING DI TOKO LISTRIK - Agus Dwi Janarko; Tri Irawati; Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2022)
Madiun electricity shop is trading company which provides electricity goods. The purpose of this study is to develop a supplier selection decision support system application which is help the administrative officer to make decision based on the highest level. The simple additive weighting method applied to know each weight based on criteria and proceed with ranking which will select alternatives. The results of the research create a support system application which is select the best supplier based on the highest level. It is according to the calculations using the Simple Addtive Weighting method. The results show that the highest supplier level is on